A new contribution to the raptorial ciliate genus Lacrymaria (Protista: Ciliophora): a brief review and comprehensive descriptions of two new species from Changjiang Estuary - Tang, Jin; Zhang, Gongaote; Guo, Junqi; Luo, Lingxuan; Jiang, Jiamei; Pan, Hongbo (Frontiers in Microbiology, 2023)
Ciliates serve as excellent indicators for water quality monitoring. However, their utilization is hindered by various taxonomic confusions. The ciliate genus Lacrymaria Bory de Saint-Vincent, 1824 is commonly found in different aquatic habitats, but its taxonomy has been sparsely investigated using state-of-the-art methods. This study investigated two new Lacrymaria species from Nanhui Wetland, Shanghai, China, using living observation, protargol staining, and molecular phylogeny methods. Lacrymaria songi sp. nov. is 180-340 × 20-25 µm in size and possesses 12-16 somatic kineties, a single terminal contractile vacuole, two macronuclear nodules and two types of rod-shaped extrusomes. Lacrymaria dragescoi sp. nov. is distinguished from its congeners by its cell size of 210-400 × 25-35 µm, 14-17 somatic kineties, a single terminal contractile vacuole, one macronucleus, and two types of rod-shaped extrusomes. Phylogenetic analyses based on SSU rRNA gene sequences indicate that Lacrymariidae is monophyletic but Lacrymaria is not. Additionally, a brief review of the genus Lacrymaria is provided. It is suggested that L. bulbosa Alekperov, 1984, L. lanceolata Kahl, 1930 and L. ovata Burkovsky, 1970 be removed from the genus, and Phialina lanceolata nov. comb. and Phialina ovata nov. comb. be proposed for the latter two.